Cloud Architectures Encountering Data Security and Privacy Concerns- A Survey - Shweta Singh (AG Volumes, 2022)
Emerging as one of the most relevant IT paradigms of recent times is cloud computing. The IT environment is increasingly being transformed by cloud computing. Cloud users may access resources, apps, including infrastructure from cloud providers on the pay-as-you-go basis. As an example, cloud providers may already have apps in place for their customers to utilise. As an example, the cloud service provider may provide the capacity to design and the deploy user apps. The Massive storage infrastructure is also accessible for such database and any user provided data. There are a slew of different cloud designs, and more are on the way. SaaS, PaaS, as well as IaaS are by far the most common, and they may be set up in private, public, communal, or a mix of these environments. It explores current cloud computing architectural advances and gives a review of numerous investigations undertaken insidecloud computing industry to address various dangers inside its design, with specific reference towards multi-cloud architectures.